BIOGRAPHY GENRE IN RUSSIAN LITERATURE: EUROPEAN AND BRITISH INFLUENCES - Eugenia V. Ivanova (Studia Litterarum)
The article examines the development of the genre of biography and life writing that influenced Russian biographical tradition. This tradition stems from Plutarch’s Comparative Biographies that influenced English life writing represented by such names as James Boswell, Lytton Strachey, and others. Philosophical premises of the English biography genre are to be found in the treatise Heroes, HeroWorship, and The Heroic in History (1841) by Thomas Carlyle. French tradition represented by Gaston Tissandier’s book Science Martyrs pursued the opposite aim: to honor ordinary scientists and inventors, responsible for the technical advance of the modern civilization. Wilhelm Dilthey and Georg Simmel practiced a different approach to life writing in that they conceived biography as the history of the person’s spiritual development. This conception had direct influence on the theorists of biography genre in Russia, G. O. Vinokur, and A. G. Gabrichevsky.